The efficacy of acupuncture for post-stroke dysphagia: an overview of systematic reviews and meta-analyses - Xu, Fangyuan; Wang, Xuepeng; Dai, Fan; Ye, Yu; Su, Xingxing; Hu, Peijia; Cheng, Hongliang (Frontiers in Neuroscience, 2025)
BackgroundAcupuncture has been widely used in clinical rehabilitation as an adjunctive therapy for post-stroke dysphagia (PSD). Although numerous meta-analyses (MAs) have evaluated its efficacy, a comprehensive assessment of the methodological quality and evidence strength of these MAs is still lacking.MethodsTwo researchers independently searched eight databases for relevant literature, screened studies according to predefined inclusion and exclusion criteria, and extracted data from the eligible systematic reviews (SRs) and MAs. The methodological quality, reporting completeness, risk of bias, and strength of evidence were rigorously evaluated using the AMSTAR 2, PRISMA-A, ROBIS, and GRADE, respectively. In addition, the GROOVE tool was used to assess the degree of overlap among original studies by calculating corrected covered area (CCA).ResultsThis overview included 19 MAs. Based on AMSTAR 2, four studies were rated as low quality, while 14 were rated as critically low quality. In terms of reporting quality, major deficiencies were observed, including a lack of protocol registration, incomplete search strategies, inadequate risk of bias assessments, and missing funding disclosures. For risk of bias, only six studies were judged to be at low risk. Furthermore, it revealed a slight overlap among the original studies with a CCA of 2.86%. Among the 68 outcome indicators, only 11.76% were graded as moderate quality, while 50% were classified as low quality and 38.24% as critically low quality, according to the GRADE assessment. Among the moderate-quality outcomes, electroacupuncture combined with swallowing rehabilitation therapy (SRT) demonstrated superior effectiveness compared to SRT alone (OR = 5.40, 95% CI: 3.78–7.72), as did acupuncture plus SRT (RR = 1.26, 95% CI: 1.19–1.34). Significant improvements in swallowing function were also reported, as measured by scales such as the Water Swallowing Test (WMD = −0.69, 95% CI: −0.78 to −0.60) and the Penetration Aspiration Scale (MD = −1.02, 95% CI: −1.27 to −0.78).ConclusionWhile acupuncture appears to be a promising adjunctive treatment for PSD, the overall quality of evidence remains low. More rigorously designed and transparently reported studies are needed to strengthen the evidence base and support clinical decision-making.